Shifts in the Gut Microbiota Composition Due to Depleted Bone Marrow Beta Adrenergic Signaling Are Associated with Suppressed Inflammatory Transcriptional Networks in the Mouse Colon - Yang, Tao; Ahmari, Niousha; Schmidt, Jordan T.; Redler, Ty; Arocha, Rebeca; Pacholec, Kevin; Magee, Kacy L.; Malphurs, Wendi; Owen, Jennifer L.; Krane, Gregory A.; Li, Eric; Wang, Gary P.; et al. (Frontiers in Physiology, 2017)
The brain-gut axis plays a critical role in the regulation of different diseases, many of which are characterized by sympathetic dysregulation. However, a direct link between sympathetic dysregulation and gut dysbiosis remains to be illustrated. Bone marrow (BM)-derived immune cells continuously interact with the gut microbiota to maintain homeostasis in the host. Their function is largely dependent upon the sympathetic nervous system acting via adrenergic receptors present on the BM immune cells. In this study, we utilized a novel chimera mouse that lacks the expression of BM beta1/2 adrenergic receptors (b1/2-ARs) to investigate the role of the sympathetic drive to the BM in gut and microbiota homeostasis. Fecal analyses demonstrated a shift from a dominance of Firmicutes to Bacteroidetes phylum in the b1/2-ARs KO chimera, resulting in a reduction in Firmicutes/Bacteroidetes ratio. Meanwhile, a significant reduction in Proteobacteria phylum was determined. No changes in the abundance of acetate-, butyrate-, and lactate-producing bacteria, and colon pathology were observed in the b1/2-ARs KO chimera. Transcriptomic profiling in colon identified Killer Cell Lectin-Like Receptor Subfamily D, Member 1 (Klrd1), Membrane-Spanning 4-Domains Subfamily A Member 4A (Ms4a4b), and Casein Kinase 2 Alpha Prime Polypeptide (Csnk2a2) as main transcripts associated with the microbiota shifts in the b1/2-ARs KO chimera. Suppression of leukocyte-related transcriptome networks (i.e. function, differentiation, migration), classical compliment pathway, and networks associated with intestinal function, barrier integrity, and excretion was also observed in the colon of the KO chimera. Moreover, reduced expression of transcriptional networks related to intestinal diseases (i.e. ileitis, enteritis, inflammatory lesions and stress) was noted. The observed suppressed transcriptome networks were associated with a reduction in NK cells, macrophages, and CD4+ T cells in the b1/2-ARs KO chimera colon. Thus, sympathetic regulation of BM-derived immune cells plays a significant role in modifying inflammatory networks in the colon and the gut microbiota composition. To our knowledge, this study is the first to suggest a key role of BM b1/2-ARs signalling in host-microbiota interactions, and reveals specific molecular mechanisms that may lead to generation of novel anti-inflammatory treatments for many immune and autonomic diseases as well as gut dysbiosis across the board.